Application in Lieu of Money Penalty to Corruption Actors Based on Act No. 31 of 1999 jo. Act No. 20 of 2001 on Combating Crime of Corruption - Joko Hermawan Sulistyo; Jawade Hafidz (Jurnal Daulat Hukum, 2018)
Corruption resulted in losses to the state, resulting in the combating creation also sought refund of the state financial losses. Imprisonment and fined, have not been able to restore the country's financial losses due to corruption, and have not been able to take money from the corruption of the perpetrators, so it needs an additional form of criminal punishment imposed for compensation. Compensation will be imposed by the judge, as much as possible the amount equal to the property magnified by of corruption. Convicts are given a grace period of one month already se-binding court decision to pay it off. If within this period has ended, then the prosecutor as an executor of the state may seize and auction off property of the accused. However, in criminal application for compensation, there are still obstacles, among which is the difficulty to trace the perpetrators of corruption money and annihilate, use / divert money of corruption in other forms. Efforts to do is to foreclosure and auction of property belonging to criminal and his heirs, ruling subsidiary imprisonment, as well as a civil lawsuit and financial administration.Keywords: Crime; Money Substitutes; and Corruption.